2013
DOI: 10.1186/1471-2164-14-405
|View full text |Cite
|
Sign up to set email alerts
|

Cubilin expression is monoallelic and epigenetically augmented via PPARs

Abstract: BackgroundCubilin is an endocytic receptor that is necessary for renal and intestinal absorption of a range of ligands. Endocytosis mediated by cubilin and its co-receptor megalin is the principal mechanism for proximal tubule reabsorption of proteins from the glomerular filtrate. Cubilin is also required for intestinal endocytosis of intrinsic factor-vitamin B12 complex. Despite its importance, little is known about the regulation of cubilin expression.ResultsHere we show that cubilin expression is under epig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 71 publications
2
26
0
Order By: Relevance
“…The enhanced green fluorescent protein (EGFP)-expressing proximal tubule cells are cubilin deficient, and their brush borders had significantly less bound albumin than proximal tubules with WT cubilin expression. 26 Similarly, we show here that apoA-I localization in the brush border of EGFP-expressing cubilindeficient proximal tubules in the Cubn heterozygous mouse kidney is greatly reduced (Figure 8). The level of apoA-I localization to proximal tubule brush borders was quantified by counting the number of proximal tubules with detectable apoA-I immunofluorescence in 109 images from four WT and five HT mice.…”
Section: Effect Of Cubilin Deficiency On Apoa-i Localization In Kidnementioning
confidence: 78%
See 1 more Smart Citation
“…The enhanced green fluorescent protein (EGFP)-expressing proximal tubule cells are cubilin deficient, and their brush borders had significantly less bound albumin than proximal tubules with WT cubilin expression. 26 Similarly, we show here that apoA-I localization in the brush border of EGFP-expressing cubilindeficient proximal tubules in the Cubn heterozygous mouse kidney is greatly reduced (Figure 8). The level of apoA-I localization to proximal tubule brush borders was quantified by counting the number of proximal tubules with detectable apoA-I immunofluorescence in 109 images from four WT and five HT mice.…”
Section: Effect Of Cubilin Deficiency On Apoa-i Localization In Kidnementioning
confidence: 78%
“…Previously, we showed that cubilin expression is monoallelic. 26 Thus, proximal tubules in the Cubn heterozygous mice stochastically express either the targeted Cubn allele (containing the EGFP cassette) or the WT cubilin allele. The enhanced green fluorescent protein (EGFP)-expressing proximal tubule cells are cubilin deficient, and their brush borders had significantly less bound albumin than proximal tubules with WT cubilin expression.…”
Section: Effect Of Cubilin Deficiency On Apoa-i Localization In Kidnementioning
confidence: 99%
“…However, both these proteins have multiple regulatory pathways, i.e., phosphorylation, glycosylation, which have been shown to impact their function and may be occurring during the protein overload. [38][39][40][41][42][43][44][45] A regulatory switch to reduce albumin uptake following acute albumin intake would be advantageous for maintaining a healthy kidney and overall homeostasis. Similarly, a mechanism to increase protein uptake following a transient increase in GSC for albumin would serve to maintain serum albumin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, random monoallelic gene expression is not limited to cell culture systems, but also occurs in vivo [8,21,22,28]. RNA-FISH in peripheral blood cells demonstrated that the monoallelically expressed genes identified in human B-lymphoblasts were not a consequence of long term culturing or clonal expansion of single cells [22].…”
Section: Characteristics Of Monoallelically Expressed Genesmentioning
confidence: 99%
“…A follow-up study using sensitive single-cell RT-PCR analysis, as well as FISH, confirmed monoallelic expression for the interleukins, but not for Pax5 [17], suggesting that the initially observed monoallelic expression was due to the failure to adequately detect both alleles of this sparsely expressed transcript. Additional examples of random monoallelic expression of autosomal genes in a wide range of cell types have continued to emerge: the cell adhesion molecule p120 catenin , was reported to be monoallelically expressed in both lymphoblasts and fibroblasts [18]; the glial fibrillary acidic protein Gfap in cortical astrocytes [19]; Igf2bp1 , a zinc finger protein required for imprinted expression of the Igf2 gene, in B cells [20]; and recently Cubilin , an endocytic receptor, was shown to be monoallelically expressed in renal proximal tubules and small intestine [21]. What is apparent from all of these isolated examples, is that genes of a wide range of functions can be monoallelically expressed in different cell types.…”
Section: Introductionmentioning
confidence: 99%